No Difference in Recovery of Patient-Reported Outcome and Range of Motion between Cruciate Retaining and Posterior Stabilized Total Knee Arthroplasty: A Double-Blind Randomized Controlled Trial - van den Boom, Lennard G. H.; Brouwer, Reinoud W.; van den Akker-Scheek, Inge; Reininga, Inge H. F.; de Vries, Astrid J.; Bierma-Zeinstra, Sita M. A.; van Raay, Jos J. A. M. (The Journal of Knee Surgery, 2019)
Both from the perspective of the individual and from a socioeconomic point of view (e.g., return to work), it is important to have an insight into the potential differences in recovery between posterior cruciate ligament retaining (PCR) and posterior stabilized (PS) total knee arthroplasty (TKA) implants. The primary aim of this study was to compare the speed of recovery of patient-reported outcome between patients with a PCR and PS TKA during the first postoperative year. The secondary aim was to compare the effect on range of motion (ROM). In a randomized, double-blind, controlled, single-center trial, 120 adults diagnosed with osteoarthritis of the knee were randomized into either the PCR or PS group. Primary outcome was speed of recovery of patient-reported pain and function, measured with the Western Ontario and McMaster Universities osteoarthritis index (WOMAC), with a follow-up of 1 year. Main secondary outcome measure was ROM. A generalized estimating equations (GEE) analysis was used to assess whether there was a difference over time between groups (“p-value for interaction”). Between 2008 and 2011, 59 participants received a PCR TKA (mean age, 70.3 years [SD = 7.7]; mean body mass index [BMI], 30.5 kg/m2 [SD = 5.4]) and 55 participants a PS TKA (mean age, 73.5 years [SD = 7.0]; mean BMI, 29.2 kg/m2 [SD = 4.4]). Six patients (two PCR and four PS) were excluded because of early drop-out, so 114 patients (95%) were available for analysis. In between group difference for total WOMAC score was −1.3 (95% confidence interval [CI]: −5.6 to 3.1); p-value for interaction was 0.698. For ROM, in between group difference was 1.1 (95% CI: −2.6 to 4.7); p-value for interaction was 0.379. These results demonstrated that there are no differences in speed of recovery of WOMAC or ROM during the first postoperative year after PCR or PS TKA.
Keywords: knee arthroplasty; posterior cruciate ligament; posterior stabilized